Applicability of the Deed of Agreement for Unilateral Termination of the Build Operate Transfer (Bot) Cooperation Agreement After the Court's Decision - Rostna Qitabi Anjilna (Authentica, 2022)
The Government of Indonesia uses the Regional Revenue and Expenditure Budget to finance infrastructure development and regional development. To avoid high development costs, the government opens up opportunities for the private sector to invest in state assets (land) with the Build Operate Transfer system (hereinafter referred to as BOT). In the BOT model, the government permits the private sector to build and operate the project for a certain period. As an unnamed agreement, there has been no specific arrangement regarding cooperation with the BOT system. Therefore, the BOT agreement was born based on the freedom of contract as regulated in Article 1338 of the Civil Code. This agreement tends to cause legal problems such as unlawful acts. This research method is normative with secondary data sources using primary, secondary, and tertiary legal materials. In the event of unilateral termination of the BOT agreement, it still refers to Article 1266 of the Civil Code. If one of the parties has not fulfilled all the elements contained in Article 1266, the responsibility for unilateral termination is compensation. Keywords: Unilateral Termination; Build Operate Transfer, Enforcement of Deed of Agreement